Advantages and important of innovation - Lai, Kong Seng; Yusof, Nor’Aini; Zainul Abidin, Nazirah (2008)
The purpose of this paper is to identify the advantages and important of innovation in housing development in Malaysia. In the pass few years, innovation became one of the hot topic among the scholar and the industry itself. In order to survive and sustain due to the globalization and uncertainty occurred in the market, the industry must do something. The industry has to reconsider the conventional and ordinary method of business. According to Porter (1980), innovation plays a crucial role in securing sustained competitive advantage. Although the market keeps mentioning innovation, but does the market ask what make innovation become crucial? What make innovation is the key of survive? What make innovation the influencer to the direction of an organization? Among these question, the most important question is what is the benefit and important of innovation? There must be a reason to practice innovation in organizational instead of just maintain the conventional and current situation. The industry especially housing development seems to be quite slow and lack of innovation. Therefore, it become crucial to explore and identify what is the advantages and important of innovation. The result of this paper should be able to reveal the benefit of applying innovation in their business. On the other hand, this paper also tries to identify the important of innovation. In addition, the housing development can has a clear view on innovation and how innovation can improve their performance. And through this paper, the housing development can take this as reference in their strategic planning for short and long term.